Pemahaman Aspek-Aspek dalam Hakikat Sains (Nature of Science) oleh Guru Sekolah Dasar di Wilayah 4P (Pedalaman, Perbatasan, Perkotaan, dan Pesisir) - Annisa, Muhsinah; -, Listiani (Jurnal Ilmiah Sekolah Dasar, 2017)
Nature of Science knowledge understanding can be related to natural science conceptual understanding. It is expected that having understanding in nature of science concepts will minimize misconception in science concepts. Therefore, every teacher should understand aspects on nature of science. Because of the importance of nature of science, a research on elementary school teachersâ understanding on nature of science in 4P areas (rural, bordered, coastal, and urban) should be done. This research is aimed to to know the use of View of Nature of Science form B that has been translated and adapted to Bahasa Indonesia. This is qualitative research, in which focusing on evaluating elementary school teachersâ view of nature of science and the use of transadapted VNOS form B questionnaire that has been developed by Lederman and El-Khalick in the USA. Indeed, there are six aspect of Nature of Science that has been measured using VNOS form B. The result shows that most of respondents are naÃ¯ve in understanding those six NOS aspects.Â